Synthesis of acid-soluble spore proteins by Bacillus subtilis. - Leventhal, J M (American Society for Microbiology (ASM), 1982)
The major acid-soluble spore proteins (ASSPs) of Bacillus subtilis were detected by immunoprecipitation of radioactively labeled in vitro- and in vivo-synthesized proteins. ASSP synthesis in vivo began 2 h after the initiation of sporulation (t2) and reached its maximum rate at t7. This corresponded to the time of synthesis of mRNA that stimulated the maximum rate of ASSP synthesis in vitro. Under the set of conditions used in these experiments, protease synthesis began near t0, alkaline phosphatase synthesis began at about t2, and refractile spores were first observed between t7 and t8. In vivo- and in vitro-synthesized ASSPs comigrated in sodium dodecyl sulfate-polyacrylamide gels. Their molecular weights were 4,600 (alpha and beta) and 11,000 (gamma). The average half-life of the ASSP messages was 11 min when either rifampin (10 micrograms/ml) or actinomycin D (1 microgram/ml) was used to inhibit RNA synthesis. IMAGES: